The History of Worldview in Secular, Christian, and Islamic Intellectual Discourse - Fadhil Sofian Hadi; Hasrul Sani; Najib R.K. Allaham (University of Darussalam Gontor, Indonesia, 2021)
This paper is focused to observe the history of the bustling worldview studied by contemporary academics. There are different definitions and terms of worldview used by the figures who carry the term and are certainly influenced by their respective belief systems. The definition of worldview will be different if it is used in terms of religion, language, science, philosophy, and others. Due to differences in the background, then defining worldview to be diverse. The historical analysis approach is used as a method in writing that departs from different views. With a historical approach used as a method in writing that departs from different views, This paper is presented to clarify the difference in the worldview from the point of view of the figures as an affirmation that the world view is a value-laden concept and is important in contemporary scientific discourse. As a result, the view of the world (worldview) of each of these individuals has an impact on their thoughts, feelings, actions in life activities.